MENTORING ON EFFECTIVE CLASSROOM MANAGEMENT STRATEGIES FOR TEACHERS OF MADRASAH DINIYAH MAMBAUL ULUM BULANGAN HAJI PEGANTENAN PAMEKASAN - Abd Qadir, Ach. Mahfudz (PT Altin Riset Publishing, 2025)
This service research aims to improve teachers' skills in managing the classroom effectively in Madrasah Diniyah Mambaul Ulum Bulangan Haji Pegantenan Pamekasan, while creating a conducive and interactive learning atmosphere. The background of this activity departs from the initial conditions of learning, which are still dominated by the one-way lecture method, low student participation, and suboptimal classroom behavior management. Through a systematic mentoring approach, this research uses a participatory action research (PAR) method that actively involves teachers starting from the problem identification stage, training, simulation, direct practice in the classroom, to evaluation. The implementation of mentoring includes providing training on the concept of Classroom Management, simulating classroom management strategies, arranging learning spaces, applying varied learning methods, and utilizing positive reinforcement. Research data were obtained through observation, interviews, and documentation, then analyzed descriptively and qualitatively. The results showed a significant increase in teacher skills, including the application of clear class rules, variations in learning methods, increased teacher-student interaction, and the use of media and spatial arrangements that better support collaboration. Student participation increased, disruptive behavior decreased, and the classroom atmosphere became more conducive. Supporting factors for success include teacher motivation, support from madrasah administrators, and positive acceptance from santri, while inhibiting factors are limited facilities and adaptation to new methods. In conclusion, effective classroom management strategies can be implemented well in traditional madrasah diniyah, have a positive impact on the quality of learning, and are relevant to be adopted in similar educational institutions.